Aloe polysaccharide protects skin cells from UVB irradiation through Keap1/Nrf2/ARE signal pathway. (2nd April 2020) - Yuan, Lingling; Duan, Xingwu; Zhang, Runtian; Zhang, Yunbi; Qu, Muwen
Abstract: The aim of this study was to investigate if aloe polysaccharide (AP) has the repairing effect on ultraviolet b (UVB) injured nerve cells. The study applied BALB/c female mice as animal model, and NFG-activated PC12 cells as cell model of skin nerve. The cell viability was detected by MTT assay, and cell apoptosis was detected by TUNEL (TdT-mediated dUTP nick-end labeling) and Annexin-V/PI assay, and cell-cycle status in different groups were observed via flow cytometry (FCM). Enzyme-linked immunosorbent assay (ELISA) was applied to analyze oxidative stress and anti-oxidative ability in each group. Real-time PCR and western blot were used to detect the expression levels of Bax, Bcl-2, Caspase-3, Cyclin D1, Keap1, Nrf2, GCLC, and GSTP1. The results showed obvious inhibition of cell viability and cell-cycle progression and promotion of cell apoptosis by UVB irradiation through inducing oxidative stress. In AP treated groups, cell viability and proliferation could be markedly improved and cell apoptosis inhibited with higher anti-oxidative capability and up-regulated expression of Keap1, Nrf2, GCLC, and GSTP1. It suggested that AP was able to repair UVB induced injury on NGF activated skin neural cell PC12, probably through Keap1/Nrf2/ARE signal pathway.